ETHNIC IDENTITY IN HUETARS INDIGENOUS PEOPLE OF QUITIRRISI - Moreno Salas, Marjorie (2013)
The article explores some of the elements that are part of ethnic identity of the Huetar indigenous people in Quitirrisi of Mora by means of a quantitative methodology. To investigate such variable, 90 people from the community answered a questionnaire. The results indicated that the group maintains a high level of ethnic identity. Also, some relevant factors for keeping the cultural identity were: their traditions from ancestors, living in the reserve and the indigenous blood. The data revealed some important information since they show a different perspective about the belonging feeling to an ethnic group.